Serum Procalcitonin in the Prediction of Severity and Outcome of Acute Pancreatitis - Saqeb, Khan Md Nazmus (Bangladesh Critical Care Journal, 2021)
Background: Different modalities are available for predicting severity and outcome of acute pancreatitis. A single marker with high sensitivity and specificity is yet to be identified. Aim: This study intends to find out the utility of serum procalcitonin in predicting the severity and outcome of acute pancreatitis. Methods: 117 patients admitted with acute pancreatitis were included.Clinical parameters and biochemical tests were recorded on admission, on day-3 & day-5 of admission. CT scan was performed in all patients. Serum procalcitonin was done on admission. Multifactorial scores were calculated using these data.Every patient was followed for identification of organ failure or other complications. Statistical analysis was done with SPSS. Result: Among 117 patients, 67(57.3%) were male. Biliary, hypertriglyceridemia, alcohol, malignancy and post-ERCP complications were found as aetiology in 25(21.4%), 23(19.7%), 8(6.8%), 3(2.6%),2(1.7%) cases respectively. In 53(45.3%) cases no definite etiology could be found. 83(70.9%) patients had mild,15(12.8%) had moderately severe and 19(16.2%) had severe acute pancreatitis. 23(19.65%) patients developed complication, whereas 94 (80.34%) developed none. The mean serum procalcitonin(pg/ml) of patients with mild, moderately severe and severe disease was 146±165.21, 1297±439.44, 4361±1493.55 respectively. The difference among the groups were statistically significant. Mean serum procalcitonin(pg/ml) in patientswho developed complications was 3744±1827.05 and in those without complication it was 301±559.97.ROC curve evaluating the role of serum procalcitonin in predicting outcome of acute pancreatitis showed AUC of 0.985. A cutoff point of 1131.28pg/ml showed highest sensitivity (95.7%) & specificity (94.7%). Conclusion: Serum procalcitonin can be a new promising marker to predict severity and outcome of acute pancreatitis. Bangladesh Crit Care J March 2021; 9(1): 16-21